“Gaining Perspective”: A Photovoice Study of a Circumpolar Experience for Northern Canadian Nursing Students in Northern Norway - Bott, Gloria; Moffitt, Pertice (Quality Advancement in Nursing Education / Avancées en formation infirmière, 2025)
Purpose: The benefits of study-abroad experiences for nursing students have been well documented. Since 2010, an undergraduate nursing program in Northern Canada has had an exchange partnership with nursing schools in Northern Norway. Given the mostly anecdotally reported successes of the exchanges, this study aimed to formally investigate the educational experiences of Northern Canadian nursing students who completed a clinical practicum and cultural experience in Northern Norway.Methods: This qualitative study employed photovoice methodology. As photovoice is participatory action research (PAR), students learned about the methodology prior to embarking on their international exchange. While abroad, they engaged in photographic documentation that later served as a catalyst for data collection (interviews and focus group) and data analysis. Aligned with PAR, students participated with the researchers in data analysis. Moreover, the photos and stories later served as a tool to bring about action; specifically, the students endorsed future exchanges.Results: Four nursing students (n = 3 in third year; n = 1 in fourth year) who completed a 7-week course in Northern Norway during 2023 participated in this study. Thematic analysis revealed “gaining perspective” as the overarching theme. Three subthemes highlighted other ways of knowing, being, and doing for nursing practice and life.Conclusion: Similar to other evidence supporting study-abroad experiences for nursing students, this opportunity for Northern Canadian nursing students in another circumpolar country offered professional and personal learning.